Protein adsorption, platelet adhesion, and bacterial adhesion to polyethylene‐glycol‐textured polyurethane biomaterial surfaces. Issue 3 (16th December 2015) - Xu, Li‐Chong; Siedlecki, Christopher A.
Abstract: Traditional strategies for surface modification to enhance the biocompatibility of biomaterials often focus on a single route utilizing either chemical or physical approaches. This study combines the chemical and physical treatments as applied to poly(urethane urea) (PUU) biomaterials to enhance biocompatibility at the interface for inhibiting platelet‐related thrombosis or bacterial adhesion‐induced microbial infections. PUU films were first textured with submicron patterns by a soft lithography two‐stage replication process, and then were grafted with polyethylene glycol (PEG). A series of biological response experiments including protein adsorption, platelet adhesion/activation, and bacterial adhesion/biofilm formation showed that PEG‐grafted submicron textured biomaterial surfaces were resistant to protein adsorption, and greatly increased the efficiency in reducing both platelet adhesion/activation and bacterial adhesion/biofilm formation due to the additive effects of physical topography and grafted PEG. Results suggest that a combination of chemical modification and surface texturing will be more efficient in preventing biomaterial‐associated thrombosis and infection of biomaterials. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 668–678, 2017.